2019
DOI: 10.1063/1.5111289
|View full text |Cite
|
Sign up to set email alerts
|

Effects of trapping site on the spectroscopy of 1P1 excited group 12 metal atoms in rare gas matrices

Abstract: The role of spin-orbit coupling in the optical spectroscopy of atomic sodium isolated in solid xenon Low Temperature Physics 45, 715 (2019);

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…In the present work we have selected the lighter Group 12 metal atoms zinc and cadmium because, like their fellow‐group member mercury, they are small metal atoms where single vacancy (SV) site occupancy occurs and greatly dominates over multi‐vacancy sites. This simple site occupancy has been firmly established in recent molecular dynamics simulations [3] of the growth of SRG samples doped with the guest atoms Zn, Cd and Hg. In the three rare gases Ar, Kr and Xe simulated depositions indicated that the site occupied was exclusively SV for Zn and Hg, while it dominated (Ar and Kr ∼90 %) in Cd.…”
Section: Introductionmentioning
confidence: 66%
See 4 more Smart Citations
“…In the present work we have selected the lighter Group 12 metal atoms zinc and cadmium because, like their fellow‐group member mercury, they are small metal atoms where single vacancy (SV) site occupancy occurs and greatly dominates over multi‐vacancy sites. This simple site occupancy has been firmly established in recent molecular dynamics simulations [3] of the growth of SRG samples doped with the guest atoms Zn, Cd and Hg. In the three rare gases Ar, Kr and Xe simulated depositions indicated that the site occupied was exclusively SV for Zn and Hg, while it dominated (Ar and Kr ∼90 %) in Cd.…”
Section: Introductionmentioning
confidence: 66%
“…From previous experimental [22] and theoretical work [3] it is known that the pairs of bands present in the recorded emission spectra in the annealed matrix systems Zn/Ar, Zn/Kr and Cd/Kr are not related to a multiple site occupancy. In all of these cases the emission characteristics are well reproduced with the contributions arising only from metal atom occupancy in sv sites.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations